Affective mapping of EEG during executive function tasks - Othman, Marini, Abdul Qayoom; Abdul Rahman, Abdul Wahab (2012)
Executive function is a set of mental processes commonly linked with the activation of the brain’s prefrontal cortex. While many studies have focused on EF in adulthood, the development of EF in children is yet to be understood. This paper proposes a new approach for understanding children’s reactions during EF tasks by mapping their EEG signals onto the 2D valence-arousal affective space model. Brain signals of ten pre-school children aged between 4-6 years (male: 5; female: 5) were collected while they play the standardized version of the Dimensional Change Card Sort. Behavioral results in terms of percentage of correct responses and response time did not vary significantly across gender. Emotion mapping using the valence-arousal model showed that boys tend to be consistent in their emotion during preswitch and post-switch tasks. The emotion of girls, however, tends to shift towards neutral state during the post-switch test regardless of their initial emotions in the pre-switch phase.